2019
DOI: 10.31557/apjcp.2019.20.10.3113
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life among Egyptian Female Breast Cancer Patients at the National Cancer Institute, Cairo University

Abstract: Population-Based Cancer Registry Program in Egypt (2008-2011); BC is the most common cancer in females representing about 32% of all female malignancies with the crude and age-standardized incidence rates of 35.8 and 48.8 per 100,000 population, respectively (Ibrahim et al., 2014).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
2
4
1
Order By: Relevance
“…Age had no significant association with EORTC QLQ-C30 symptom scales. On contrary to our study, age had a significant association with Functional Assessment of Cancer Therapy-Breast questionnaire (FACT B-4) breast cancer QoL assessment tool [37]. This discrepancy between studies might be due to the variation in socioeconomic status, and different QoL assessment tools.…”
Section: Factors Associated To Qol Of Breast Cancer Patientscontrasting
confidence: 99%
See 2 more Smart Citations
“…Age had no significant association with EORTC QLQ-C30 symptom scales. On contrary to our study, age had a significant association with Functional Assessment of Cancer Therapy-Breast questionnaire (FACT B-4) breast cancer QoL assessment tool [37]. This discrepancy between studies might be due to the variation in socioeconomic status, and different QoL assessment tools.…”
Section: Factors Associated To Qol Of Breast Cancer Patientscontrasting
confidence: 99%
“…In the present study, patients who had comorbidity had also more insomnia ( p = 0.029), appetite loss ( p = 0.014), and diarrhoea ( p = 0.007). A study conducted in Cairo had showed patients who had no comorbidities had significantly higher social wellbeing ( p = 0.014) and FWB ( p = 0.004) scores than those who had comorbidities [ 37 ]. Similarly in our study, patients who had no comorbidity had better physical function ( p < 0.001), cognitive function ( p = 0.013), and social function ( p = 0.009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The health-related QoL of 200 Egyptian female breast cancer patients is measured using the functional assessment of cancer therapy-breast for patients with lymphedema in the medical oncology outpatient clinic between December 2015 and March 2018 [22]. The median assessment score is 81 (range 35-133).…”
Section: Discussionmentioning
confidence: 99%
“…3 Also, in comparison to younger age groups, the older age group had a significantly higher score on the BC subscale. 4 When compared to the United States (14.7 per 100,000), Egyptian breast cancer patients had a higher mortality rate (20.1 per 100,000). 5 Immunology of BC suggests a dual role of immune cells, including tumour-suppressive or immunosuppressive effect, according to the carcinogenic environment signals.…”
Section: Introductionmentioning
confidence: 98%